Simple process for lithium extraction from α-spodumene with potassium fluoride: Modeling and optimization - Rosales, Gustavo Daniel; Resentera Beiza, Alexander Cristian Jesús; Braga, Paulo; Esquivel, Marcelo Ricardo Oscar; Rodriguez, Mario Humberto (Institution of Chemical Engineers, 2023)
Fil: Rosales, Gustavo Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Interdisciplinario de Ciencias Básicas. - Universidad Nacional de Cuyo. Instituto Interdisciplinario de Ciencias Básicas; Argentina